2012
DOI: 10.3892/or.2012.1691
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of OTP gene as a novel methylation marker of breast cancer

Abstract: Abstract. Aberrant DNA methylation occurs early and frequently in tumorigenesis. Identification of DNA methylation biomarkers is a field that provides potential for improving the clinical process of breast cancer diagnosis. We utilized a genome-wide technique, methylated DNA isolation assay (MeDIA), in combination with high-resolution CpG microarray analysis to identify hypermethylated genes in breast cancer. Among differentially methylated genes between tumor and adjacent normal tissues, 3 candidate genes (LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…McGregor et al has previously reported that WT1 expression was up-regulated in BC cells ( McGregor et al, 2018 ), which was consistent with our findings. Furthermore, we found that WT1 exhibited hypermethylation in BC tissues, which was consistent with the results reported by Kim et al (2012) . Compared to Kim’s research which was performed on BC cells and a single subtype of BC, our study additionally showed that WT1 was highly expressed and hypermethylation in all the four subtypes of BC.…”
Section: Discussionsupporting
confidence: 92%
“…McGregor et al has previously reported that WT1 expression was up-regulated in BC cells ( McGregor et al, 2018 ), which was consistent with our findings. Furthermore, we found that WT1 exhibited hypermethylation in BC tissues, which was consistent with the results reported by Kim et al (2012) . Compared to Kim’s research which was performed on BC cells and a single subtype of BC, our study additionally showed that WT1 was highly expressed and hypermethylation in all the four subtypes of BC.…”
Section: Discussionsupporting
confidence: 92%
“…We chose a diverse set of genes and two DNA repeats (Table 1 ) to assay for DNA methylation in cancer, adjacent and control mammoplasty tissues. Eight of the 23 examined DNA regions overlapped or were near regions previously reported to be hypermethylated in breast cancer vs. non-cancerous breast tissue, namely, EGFR [ 20 ], GSTP1 [ 21 ], LHX2 [ 22 ], PITX2 [ 23 ], RASSF1A [ 24 ], RUNX3 [ 25 ], APC [ 26 ] and BRCA1 [ 27 , 28 ] or hypomethylated in breast cancer vs. normal breast, namely, TFF1 [ 29 ], satellite 2 and LINE-1, DNA repeats [ 30 , 31 ]. In addition, the first six of the above-mentioned gene regions displayed hypermethylation in one or two breast cancer cell lines (MCF-7 and T-47D) relative to a human breast epithelial cell culture derived from normal breast tissue (human mammary epithelial cells, HMEC) and compared with most normal tissues, including breast tissue as seen in whole-genome DNA methylation data (reduced representation bisulfite sequencing, RRBS) from the ENCODE project [ 5 , 13 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies have also compared tumor to nonmalignant tissue and the number of genes identified that discriminates the two depends on the filtering or analyses utilized. For example, Kim et al (2012) used several filtering processes to identify six genes, whereas Faryna et al (2012) identified 214 CpG islands but only one CpG island (TAC1) was methylated in all ten cancer samples. The identification of thousands of loci with altered DNA methylation between non-malignant and tumor tissue using genome wide methylation analyses raises several (Li et al 2010, Dedeurwaerder et al 2011, Fang et al 2011, Hill et al 2011, Sun et al 2011, although a study by Van der Auwera et al (2010) did not find any association between hormone receptor status and DNA methylation profile (Table 1).…”
Section: Limitations and Biases Of Genome Wide Dna Methylation Technimentioning
confidence: 99%